2004
DOI: 10.1007/bf02350990
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of single motor unit mechanomyographic response and twitch force by spike-triggered averaging

Abstract: A method for non-invasive assessment of single motor unit (MU) properties from electromyographic (EMG), mechanomyographic (MMG) and force signals is proposed. The method is based on the detection and classification of single MU action potentials from interference multichannel surface EMG signals and on the spike-triggered average of the MMG (detected by an accelerometer) and force signals. The first dorsal interosseous (FDI) and abductor digiti minimi (ADM) muscles were investigated at contraction levels of 2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 20 publications
(13 reference statements)
3
34
1
Order By: Relevance
“…Moreover, the present results provide evidence of a major role of fiber displacement in the origin of the MMG. The dependence of MMG responses on accelerometer location is in agreement with the observations that muscle morphology and architecture affects the MMG signal features [8,19,20,21,29,30].…”
Section: Physiological Implicationssupporting
confidence: 85%
“…Moreover, the present results provide evidence of a major role of fiber displacement in the origin of the MMG. The dependence of MMG responses on accelerometer location is in agreement with the observations that muscle morphology and architecture affects the MMG signal features [8,19,20,21,29,30].…”
Section: Physiological Implicationssupporting
confidence: 85%
“…During static contraction the MMG/EMG was larger at 10% than that at 20% MVC. This result may reflect the possible nonlinear summation, or destructive interference, in the MMG signal at low levels of isometric contraction when more MUs are recruited and the firing rate is increased (Orizio et al 1996;Cescon et al 2004). During the eccentric phase in the dynamic contraction at 20%MVC, the MMG/EMG ratio was significantly higher than that in the intermittent static contraction, indicating that a given EMG activity may result in a larger number of the cross bridges cycling, e.g.…”
Section: Electromyography and Mechanomyographymentioning
confidence: 76%
“…The EMG amplitude has been shown to be affected by the number and firing rate of the active MUs, the shape of the MU action potential, and the crosscorrelation of the MUs discharge (Basmajican and De Luca 1985). With regard to MMG, several papers have demonstrated that the pressure waves due to the dimensional changes of the fibres of each active MU contributes to the muscle surface oscillations detectable as MMG during voluntary contraction in humans (Gordon and Holbourn 1948;Petitjean and Maton 1995;Yoshitake and Moritani 1999) even if, when several MUs are active, the individual motor unit contributions are summed into the MMG in a non-linear fashion (Orizio et al 1996;Cescon et al 2004). On this basis it can be assumed that during voluntary contractions the MMG origin is intrinsic to the muscle (Stokes and Blythe 2001;Søgaard et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The latencies and durations of the displacement MMG were revealed. Cescon et al recorded the MMGs from the first dorsal interosseous muscle and abductor digiti minimi muscle with an accelerometer [1]. The MMG peakto-peak value and mean power frequency were reported.…”
Section: Introductionmentioning
confidence: 99%